Effects of various warm-up protocol on special judo fitness test performance - Lum, D. (The Journal of Strength and Conditioning Research, 2019)
The purposed of this study was to compare the effects of postactivation potentiation (PAP) on Special Judo Fitness Test (SJFT) performance using explosive exercises that activates upper and lower limbs muscles. Eleven male judo athletes (mean ± SD, age, 16-29 years; height, 170 ± 7 cm; body mass, 73 ± 16 kg) attended 4 separate sessions. The first session was used to familiarize the subjects to the experimental procedure, the SJFT, the high pull test (HPT), and the 2 explosive exercises including resistance band pull and standing broad jump. Subsequently, subjects were randomly assigned in a counterbalanced manner to either perform the upper and lower body (ULB) PAP, lower body (LB) PAP or usual competition (CON) warm-up routine before performing the HPT and SJFT. The following variables were quantified: throws performed during series A, B, and C; total number of throws; heart rate immediately and 1 minute after the test; test index; peak power; and RPE after warm-up. During series 1, number of throws performed in LB and ULB were significantly greater than CON (p = 0.05). Only ULB resulted in significantly greater number of total throws (p < 0.01) and higher peak power (p < 0.01) than CON. The RPE for both LB and ULB were significantly lower than CON (p < 0.01). Peak power was moderately correlated to total number of throws performed (r = 0.4, p = 0.05). This study suggest that performing ULB before SJFT can result in improved performance and peak power.